2018
DOI: 10.3389/fpls.2017.02228
|View full text |Cite
|
Sign up to set email alerts
|

Ca Distribution Pattern in Litchi Fruit and Pedicel and Impact of Ca Channel Inhibitor, La3+

Abstract: Calcium (Ca) deficiency in fruit causes various physiological disorders leading to quality loss. However, disorders related to Ca deficiency are not simply caused by a shortage of calcium supply. Ca distribution is also an important relation. This study examined Ca distribution pattern in fruit and pedicel in litchi (Litchi chinensis Sonn.) and the influence of Ca channel inhibitor La3+ on fruit Ca uptake and distribution. In situ distribution of Ca in the phloem and xylem tissues of the pedicel was visualized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 46 publications
5
17
0
Order By: Relevance
“…Himelrick and McDuffie (1983) suggested that Ca transport into fruit was likely via the phloem but movement of Ca inside fruit was through the xylem. Our previous study also provided evidences showing important contribution of phloem pathway to fruit Ca uptake in litchi Song et al (2018) . Brauer et al (1998) found the concentration of Ca in phloem sap in a range of 10 to 100 μM, which is far higher than that reported in cytosol.…”
Section: Discussionmentioning
confidence: 59%
See 4 more Smart Citations
“…Himelrick and McDuffie (1983) suggested that Ca transport into fruit was likely via the phloem but movement of Ca inside fruit was through the xylem. Our previous study also provided evidences showing important contribution of phloem pathway to fruit Ca uptake in litchi Song et al (2018) . Brauer et al (1998) found the concentration of Ca in phloem sap in a range of 10 to 100 μM, which is far higher than that reported in cytosol.…”
Section: Discussionmentioning
confidence: 59%
“…The present study shows that it is a universal phenomenon among plant species that pedicel has a higher Ca concentration than the fruit, although the pedicel-fruit Ca concentration gradient (3–10 times) differs among genotypes. In previous studies in litchi, we found that Ca concentration in the pedicel was ten times higher than in the fruit pericarp, and suggested that there might be a “bottleneck effect” of Ca transport in the pedicel ( Huang et al, 2006 ; Song et al, 2018 ), which results in more Ca accumulation in the pedicel when more Ca is transported toward the fruit. Thus a positive correlation between Ca in the pedicel and in the fruit should be found.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations